Relationship of scrotal circumference and testicular volume to age and body weight in the swamp buffalo (Bubalus bubalis) - Bongso, T.A.; Hassan, M.D.; Nordin, W. (Elsevier, 1984)
Scrotal circumference (SC) and testicular volume (TV) were measured in 65 swamp buffalo bulls ranging in age from 7 to 60 months and weighing 130 kg to 560 kg. Ages and body weight (BW) were recorded for each male at the time of measurement to find out if they correlated with SC and TV. SC and TV increased linearly and correlated significantly with age and BW (SC vs age: r = 0.74, p<0.01; SC vs BW: r = 0.88, p<0.01; TV vs BW: r = 0.82, p<0.01). SC measurements ranged from 15.1 ± 1.1 cm to 24.0 ± 0.4 cm for ages ranging from 10.0 ± 0.6 to 48.5 ± 6.3 months, revealing that testicular size in swamp buffaloes was very much smaller than domestic cattle. The SC norms distributed with age would be useful in the evaluation of swamp buffalo males for breeding soundness.